Evaluation of Kithul Treacle as a Potential Substrate to Grow Monascus purpureus in Preparation of Monascus-fermented Black Tea - Hasara, U.P.S.; Subasinghe, P.; Abewickrama, G.; Hettiarachchi, C.; Kaumal, M.N. (University of Colombo, 2024)
Monascus purpureus is a valuable fungal strain that produces different bioactive pigments, and it is being used to produce a variety of food products. The secondary metabolites synthesized by purpureus are used as colorants for culinary purposes, food supplements, preservatives, and traditional medicine. ...
Keywords: Monascus purpureus; Monacolin K; Black Tea Leaves; Kithul Treacle; Mycelial Growth